Os sentidos da performance e da docência à luz da Logoteoria: um estudo com professores de instrumento em duas universidades do Nordeste - Aquino, Sandra Kalina Martins Cabral de (2017)
This research aims at reflecting how university music professors are related to their musical instrument, and how it can give significance to their teaching practice. This is, in fact, a qualitative research, which is more specifically based on the History of Musical Life methodology, through the application of narrative episodic interviews on the musical path of each participant involved. The general goal consists of understanding how applied instrument professors at tertiary education in two universities of the Northeast part of Brazil establish relationships between their artistic practice to their pedagogical activities, approaching the meaning of each one of them. Based on the interviews, this research aims to collect narratives not only of the experiences of the music background of the interviewees, but also subjective and emotional aspects from them. Furthermore, the analysis includes how the interviewee personally relates to music and, above all, the its meaning of in different stages of their lives. The research has an interdisciplinary character, with theoretical reference on Psychological Science, through the concepts of Viktor Frankl on the conceptions of human motivation, anchored in the search for meaning in life, which originated the Logotheory; as well as Maslow’s Theory of Human Motivation. In the field of Music Education, based on the works by Penna, Arroyo, Vieira, Queiroz, Pellegrino, and Louro. Thus, articulating contributions from Music Education and Psychology, we discuss the construction of meaning for personal life based on the artistic and/or teaching practice. Through this prism, the Logotheory became an important tool in order to analyze the interviews, as well as discussing how the professors relate themselves to their playing and teaching activities. Through the interviews with eight professors from the area of Performance – string instruments and piano – active at the Federal University of Paraiba and the Federal University of Rio Grande do Norte, we start a discussion on the meaning of performance as well as teaching. Thus, the research intends to understand the effects of the relationship professor/performer to the teaching practices of those professionals, taking into consideration that Music Education, as a field of scientific knowledge, also has the duty to look after the perception of meaning in professional life, working conditions, growth capacity and personal improvement and, above all, on the motivations of the music professor. The discussion on the role and the acting of the university music instrument professor, besides the study on the motivations and search for meaning in life in the context of Music Education, from the perspective of Frankl and Maslow, articulating the Logotherapy and Music Education, could help to understand as well as to indicate possibilities to renovate the role of professors in the area of Music Performance.